Efeitos do Lacticaseibacillus casei 01 e seu paraprobiótico derivado de inativação por ultrassom nos parâmetros cardiometabólicos e microbiota de ratos alimentados com dieta hiperlipídica - Brandão, Larissa Ramalho (2022)
Eating habits, among other environmental factors, play a determinant role in the occurrence of several pathologies, including arterial hypertension, obesity and hypercholesterolemia. Excessive consumption of sodium and saturated fat is related to the occurrence of these pathologies in the population. The ingestion of probiotics and paraprobiotics inactivated by different methods has been associated with beneficial effects on lipid and glycemic metabolism, as well as modulation of the microbiota. The present study aimed to evaluate the effects of administration of Lacticaseibacillus casei 01 (9 log CFU/mL) and its paraprobiotic derived from ultrasound treatment (20 kHz, 40 min) for 28 days in rats under consumption of hyperlipidic diet. Insulin and glucose tolerance, biochemical tests, cardiovascular parameters and fecal microbial ecology analysis were performed at the end of the intervention (28 days). Twenty-four male Wistar rats were divided into four groups of six animals each: group control (CTL), hyperlipidic diet (HLD), hyperlipidic diet and live L. casei (HLD-LC), and hyperlipidic diet and inactivated L. casei (DHL-ILC). Administration of live and ultrasonically inactivated L. casei reduced (p <0.05) total and LDL cholesterol levels and controlled insulin resistance in the rats fed hyperlipidic diet. Live and inactivated L. casei promote increase (p <0.05) of Lachnospiraceae and Ruminoccocaceae and decrease (p <0.05) of Clostridiaceae, Enterobacteriaceae and Helicobacteriacea, attenuating the effects promoted by HLD. Administration of live L. casei prevented the increase in blood pressure (BP) while inactivated L. casei attenuated the BP increase. The results show beneficial effects of live and inactivated L. casei 01 and indicate ultrasound inactivation as effective for obtaining a paraprobiotic with functional properties comparable or better, depending on the effect measured, than those of live cells.